Effect of Bilge Keel on The Resistance Characteristic of Fishing Vessels in Benoa : A CFD Simulations Study - Tiara Asya Da Rosta; Mohammad Ridwan Utina; Nanang Setiyobudi; Dian Purnama Sari; Wiwin Sulistyawati (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Bilge keels are commonly installed on fishing vessels to improve stability and operational safety; however, their influence on calm water resistance remains insufficiently documented for hull forms representative of Indonesian fishing vessels. This study investigates the effect of bilge keel installation on the total resistance of a 33.5 m tuna longline fishing vessel reconstructed from field survey data in Benoa, Bali. The resistance performance of bar hull and bilge keel equipped configurations was evaluated using steady state CFD based on the RANS equations and validated against towing tank data at 3, 6, and 9 kn. Simulations were conducted over a range of Froude numbers from 0.09 to 0.271. Results indicate that both configurations exhibit the expected non-linear increase in resistance with speed. Under the investigated numerical conditions, the bilge keel equipped hull was predicted to produce lower total resistance than the bare hull across the evaluated speed range, with the largest reduction of approximately 18% at 6 kn. These findings suggest that, for the investigated hull and appendage arrangement, bilge keel installation may induce favorable local hydrodynamic interactions that partially offset appendage related drag.